BUMPINESS IN THE ATMOSPHERE IN IRAQ STUDY IN THE GEOGRAPHY OF CLIMATE (Journal of the College of Education for Women, 2019)
Bumpiness in the atmosphere is the vertical movement of air, whetherupward or downward movement and the bumpiness is accompanied by areasof unrest in the air and wind. And contribute to each of the coups thermalfronts, wind, wind and thunderstorms. Moreover, bumpiness is net of thereasons that lead to circumstances is appropriate to cut the wind, and thiscontributes to the formation of bumpiness in the atmosphere. The study foundthat the noon of the times, which is expected to occur where clear-airbumpiness during flights because of the warmth of the earth's surface. Thestudy found increased incidence of air hole during the summer, especiallyJuly, due to increased incidence of coup surface, while the spring occupies aspecial March, the lowest frequency of the coup-off, due to increased stability,the absence of air.The study had shown that the air hole near the earth's surface is moredangerous than those which occur at high altitudes.